2008
DOI: 10.1128/jvi.00618-08
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of TLR3 Impairs the Innate Immune Response to West Nile Virus in the Elderly

Abstract: West Nile virus (WNV), a mosquito-borne flavivirus, has recently emerged in North America, and the elderly are particularly susceptible to severe neurological disease and death from infection with this virus. We have investigated the innate immune response of primary human macrophages to WNV in vitro and have found significant differences between the responsiveness of macrophages derived from younger donors and that from older donors. Binding of the glycosylated WNV envelope protein to the C-type lectin dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
182
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(190 citation statements)
references
References 37 publications
7
182
1
Order By: Relevance
“…In line with this, passive transfer of IFN-γ or perforin-deficient T cells into RAG knockout mice did not confer any noticeable anti-WNV protection [248]. Dysregulation of TLR3 and TLR7 responses in the elderly has also been associated with enhanced vulnerability to lethal WNV infections [249,250].…”
Section: Susceptibility Factors For Arboviral Encephalitis: Lessons Fmentioning
confidence: 56%
“…In line with this, passive transfer of IFN-γ or perforin-deficient T cells into RAG knockout mice did not confer any noticeable anti-WNV protection [248]. Dysregulation of TLR3 and TLR7 responses in the elderly has also been associated with enhanced vulnerability to lethal WNV infections [249,250].…”
Section: Susceptibility Factors For Arboviral Encephalitis: Lessons Fmentioning
confidence: 56%
“…Recently, it has been shown that young patients infected with West Nile virus show reduced TLR3 expression on the surface of macrophages, while in elderly there was a dysregulation and a persistent TLR3 expression [57]. This may lead to an elevated inflammatory response causing an excess morbidity of elderly suffering from infection.…”
Section: Monocyte/macrophages Functional Changes With Agingmentioning
confidence: 99%
“…• Chemotaxis decreased or no change [15,16,17] Free radical production decrease [15,16,17] Intracellular killing decreased [15,16,17] Rescue from apoptosis decreased [18] Intracellular signalling altered [14,19,20 Free radical production decrease [56] Intracellular killing decrease [56] Pro-inflammatory cytokine production increased [47,48,54,57] Intracellular signalling altered [29,47,48,49] Dendritic cells Phenotype no change or decrease [47,63,64] Subpopulations no change [63,64] Receptors number decrease or no change [29,65] Functions Phagocytosis decrease or no change [63,72,73] Antigen presentation decreased [63,72] Chemotaxis decreased [73] Intracellular killing decrease [63] Pro-inflammatory cytokine production increased [63,66,68] T cell priming altered [63,72] Cytokine production decreased or no change [84,88] T cell priming altered …”
Section: Innate Immunosenescence and Age-associated Pathologiesmentioning
confidence: 99%
“…We have recently assessed the effects of aging on Toll-like receptors (TLRs), key components of the innate immune system that detect microbial infection and trigger antimicrobial host defense responses . We have shown dysregulation of TLR3 in macrophages and lower production of IFN by DCs from elderly donors in response to infection with West Nile virus 6,7 . Paramount to our understanding of immunosenescence and to therapeutic intervention is a detailed understanding of specific cell types responding and the mechanism(s) of signal transduction.…”
mentioning
confidence: 99%
“…In a large cohort of healthy human donors, we showed that peripheral blood monocytes from the elderly have decreased expression and function of certain TLRs 4 and similar reduced TLR levels and signaling responses in dendritic cells (DCs), antigen-presenting cells that are pivotal in the linkage between innate and adaptive immunity 5 . We have shown dysregulation of TLR3 in macrophages and lower production of IFN by DCs from elderly donors in response to infection with West Nile virus 6,7 .…”
mentioning
confidence: 99%